REDESAIN BANGUNAN DINDING PENAHAN TANAH PADA RUAS JALAN PUJON DESA NGROTO KABUPATEN MALANG - Hamimullah, Hamimullah; Suhudi, Suhudi; Sulistyani, Kiki Frida (eUREKA : Jurnal Penelitian Mahasiswa Teknik Sipil dan Teknik Kimia, 2017)
Road existing Pujon Ngroto village is one of the main roads linking the traffic flow of Malang and Kediri access is precisely on the outskirts of Konto River which empties into Selorejo Dam, the river has a flow which is quite extensive. During this time in the surrounding areas often suffer landslides and flooding in a number of points. So on this occasion the researchers want to investigate about: "Soil Retaining Walls Building Redesign On Rural Roads Pujon Ngroto Malang" Based on the survey results of research and soil testing in the laboratory is known that the building in its existing state already does not meet the safe rate and researchers are planning the retaining wall to the size of High Total H + D = 10:50 m, High Retaining Walls H = 9.00 m, width Bottom B = 4 m, width Top B = 0.50 m, depth of the foundation df = 1:50 m, secure the stability of the carrying capacity of the land, the overthrow stability, shear stability, and to the quake. Keyword : Redesign, gravity type retaining walls, dimensions, Pujon street